On some species of the genus Hygrodromicus Tronquet with description of a new species from Pakistan (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2024)
Taxonomic and faunistic data for three species of Hygrodromicus Tronquet, 1981 is presented. Two species are (re-)described and illustrated: H. incrassatus sp. n. from Pakistan and Middle Asian H. splendidus Zerche, 1992. A distribution map for these is given. A new synonymy is established: H. coriaceus (Cameron, 1924) = Hygrogeus ledouxi Coiffait, 1983 syn. n. Additionally, H. splendidus is recorded from Kazakhstan and Kyrgyzstan for the first time.